The Effect of Injection Parameters on Warpage, Shrinkage, and Tensile Strength of Polypropylene Composites - Andre Bawono, Julius; Budiarto; Kurniawan, Perwita (Jurnal Rekayasa Mesin, 2025)
Polypropylene composite material is an environmentally friendly material when compared to other polymer materials because the composition of polypropylene is only 76% and the remaining 24% is limestone. The use of this composite material is to reduce dependence on the use of Acrylonitrile Butadiene Styrene (ABS) and Acrylic Styrene (AS) resins because both materials are difficult to decompose and recycle. The "base" product made from this material has a warpage defect that causes a gap effect when the product is installed with other components. Therefore, a study was conducted on the effect of mold temperature and holding pressure on warpage defects, shrinkage, tensile strength and surface morphology. This study used an experimental method with variations in mold temperature used were 20°C, 40°C, and 60°C, variations in holding pressure used were 70 bar, 110 bar, and 150 bar. Testing was carried out by measuring dimensions to determine warpage, shrinkage percentage, measuring tensile strength and observing surface structure. The warpage value decreases by 29% at high mold temperatures and increases by 84% at high holding pressure. The shrinkage percentage decreases with increasing mold temperature and holding pressure in the transverse direction by 7.14%-9.52% at constant pressure and 25%-26.29% at constant temperature, in the longitudinal direction by 1.27%-6.21% at constant pressure and 13.92%-17.95% at constant temperature. The optimal parameters to obtain the highest tensile strength of 26.77 MPa are at a mold temperature of 60°C and a holding pressure of 110 bar.